A comparative study of production efficiency in coastal region and non-coastal region in Mainland China: An application of metafrontier model. Issue 8 (17th November 2018) - Chen, Chien-Yin; Lin, Shiue-Hung; Chou, Li-Chen; Chen, Kun-Dang
ABSTRACT: This paper examines production efficiency of coastal region and non-coastal region in Mainland China between 2000 and 2010 using one-step stochastic frontier analysis and two-step metafrontier model. Unlike previous studies, this study not only discusses production efficiencies but also considers differences in production patterns. The empirical results indicate that coastal region has better production performance in metafrontier technology efficiency (MTE) and technology gap ratio (TGR). In addition, this study finds that the gap of MTE and TGR between coastal region and non-coastal region is increasing for the past years.